Administrative Criminal Reform in Providing Accountability for Skincare Actors Who Have Not Registered with BPOM - Ifahda Pratama Hapsari; Putri, Aulia (JUSTISI, 2025)
The study aimed to analyze which problem from skincare products none approval from Indonesian Food and Drug Administration (BPOM) This is serious problem the affects public health and damages consumer trust. This study examines the legal issues and fraud risks for those running illegal skincare businesses. Based on Article 36 of the 2009 Health Law, namely Article 106 and Article 197, business owners who operate products without BPOM approval can face administrative for penal sanctions. According to the principle of strict liability, business owners must ensure the safety of their products from the beginning to the end of the production process. If consumers suffer losses as a result of undelivered products, manufacturers or distributors can be asked to provide compensation. In addition, this study highlights the role of BPOM in legal compliance and law enforcement, as well as the importance of public awareness to prevent discrimination. Methods used in this study isnormative legal research. The research aims to scientifically explain how two legal principles, strict liability and vicarious liability, are applied in the legal context involving the sale of illegal cosmetic products. Describe the difference between strict liability, which does not require proof of malicious intent, and vicarious liability, which involves the responsibility of another party through a legal relationship. Highlight how the law in Indonesia, especially in health laws and BPOM regulations, enforces legal responsibility against business actors who sell illegal cosmetics. Emphasize the importance consumer protection and liability of producers and distributors for their products sell, both through criminal and administrative channels.